ANALISA TEGANGAN LEBIH AKIBAT SURJA PETIR DARI TRANSMISI YANG MASUK KE TRAFO DAYA I 20 MVA DI GARDU INDUK 150 KV BUMI SEMARANG BARU (BSB) DENGAN METODE DIAGRAM TANGGA - Anggita Dwi Ratnasari; Sukarno Budi Utomo; Muhamad Haddin (Universitas Islam Lamongan, 2022)
Lightning surges that come from transmission lines are very dangerous for equipment in substations, especially transformers. The transformer is a very important main component of the substation. As a result of damage to the transformer will result in the distribution of electrical energy to consumers can be disrupted. The solution to this problem is to install an arrester to overcome the lightning surge voltage in order to avoid damage to the transformer at the substation. To secure the transformer at the 150 kV Bukit Semarang Baru (BSB) substation from lightning surges, it can be analyzed using four conditions. The method used is the lattice diagram method. Based on the results of the tests carried out on the I 20 MVA power transformer, the results obtained that the transformer can be protected from lightning surges with only one arrester. If installed two arresters would be even better. However, if an arrester is not installed, this condition is very dangerous because it will cause the transformer to be damaged, because the voltage that appears on the transformer is 939.06 kV, exceeding the BIL value of the transformer, which is 650 kV.